Preparation method of nano melt-blown composite filter material
In the preparation of nanomeltblown composite filter materials, the polyolefin framework with electret and the nanomeltblown layer are used for direct meltblowing and electrical electret, and ultrasonic synchronous welding is used to solve the problem of easy stretching and deformation of nanomeltblown fibers, which improves filtration efficiency and material bonding force, and reduces production costs.
Patent Information
- Application Number
- CN202411989383.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-29
AI Technical Summary
In the prior art, when preparing nanomeltblown composite filter materials, nanomeltblown fibers are prone to stretching and deforming, and the filtration efficiency decreases, and the processing process is complicated, which may lead to a decline in material performance.
A polyolefin frame with electret but not electret is used as the mesh laying layer, and the nano meltblown layer is meltblown directly on the frame, and the electroelectret and ultrasonic synchronous welding is performed simultaneously during one processing to reduce the number of rolling and unrolling of the material and improve the binding force.
The filtration efficiency of nanomeltblown composite filter materials is improved, damage and performance reduction during processing are reduced, production costs are reduced, and the adverse effects of adhesives or hot pressing on nanomeltblown fibers are avoided.
Smart Images

Figure BDA0005223298940000071 
Figure BDA0005223298940000081 
Figure BDA0005223298940000082
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of melt-blown materials, and in particular to a method for preparing a nano melt-blown composite filter material. Background Art
[0002] In the fields of nanotechnology, materials science and filtration technology, electrostatic filter materials have attracted much attention due to their high filtration efficiency and wide range of applications. Electrostatic filter materials mainly capture tiny particles in the air, such as dust and bacteria, through electrostatic adsorption. Among them, nano melt-blown technology is an important method for preparing electrostatic filter materials. By spraying nano-scale fibers onto the substrate, a uniform nanofiber network is formed, thereby improving the filtration efficiency of the filter material.
[0003] The existing technical scheme is mainly to prepare an electrostatic filter material with excellent filtering performance by combining nano melt-blown technology and electret technology. First, the existing preparation method is usually to prepare nano melt-blown fibers first, and then make the nano melt-blown fibers have a permanent charge through electret. Although this method can improve the filtering efficiency of the filter material, there are some problems, such as the nano melt-blown fibers are easy to stretch and deform, resulting in a decrease in the filtering efficiency of the filter material. Secondly, the melt-blown fibers are soft and need to be compounded with the support material before use. The conventional offline compounding technology requires multiple winding and unwinding of the nano melt-blown fibers, which increases the complexity of the processing process and may also cause damage to the nano melt-blown fibers and performance degradation. Thirdly, the electrostatic skeleton can increase the dust holding capacity of the filter, but in general, the electrostatic skeleton is produced with high output and high speed. The online electret method cannot achieve the ideal electret effect, and an offline electret method is required. Finally, when the existing technical scheme combines the nano melt-blown fibers with the substrate, adhesives or hot pressing methods are usually used. The adhesive must be compounded offline, and hot pressing will affect the filtering performance of the nano melt-blown fibers and may also cause damage to the substrate. Therefore, the existing technical solutions still face certain challenges in preparing efficient and stable nano melt-blown composite filter materials. Summary of the invention
[0004] The present invention is to overcome the above-mentioned problems existing in the nano melt-blown filter material in the prior art, and provides a preparation method of a nano melt-blown composite filter material. A polyolefin skeleton with an electret but not electret is used as a laying layer, and a nano melt-blown layer is directly melt-blown on the polyolefin skeleton layer, so as to reduce the number of winding and unwinding of the melt-blown material and reduce the stretching and deformation of the nano melt-blown fiber; the polyolefin skeleton and the nano melt-blown layer are electreted once, so as to avoid damage and performance degradation during multiple processing; the polyolefin skeleton and the nano melt-blown layer are fixed by ultrasonic synchronous welding, so as to improve the bonding force between the nano melt-blown and the substrate, avoid the influence of adhesives or hot pressing methods on the filtering performance of the nano melt-blown fiber, and also avoid greater damage to the substrate.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing a nano melt-blown composite filter material comprises the following steps: (1) placing a polyolefin skeleton containing an electret but not electret on the surface of a melt-blown receiving mesh curtain, and melt-blowing a nano melt-blown layer on the polyolefin skeleton to obtain a composite material; (2) subjecting the composite material to corona electret charging; (3) Ultrasonic compounding is performed on the composite material after corona electret to obtain the nano melt-blown composite filter material.
[0006] The present invention adopts a polyolefin skeleton with an electret but not electret as a laying layer, and the nano melt-blown layer is directly sprayed on the polyolefin skeleton, and the skeleton and the nano melt-blown layer are simultaneously electret, so that the winding and unwinding times of the nano melt-blown material can be reduced, and the nano melt-blown material is not easy to stretch and deform, thereby improving the filtration efficiency of the filter material. At the same time, the present invention uses ultrasonic welding to fix the polyolefin skeleton and the nano melt-blown layer, avoiding the influence of methods such as adhesives or hot pressing on nano melt-blown fibers and substrates, and also can reduce the processing times of the material, and the skeleton electret and melt-blown electret are completed at one time, improving production efficiency. In addition, the present invention is directly electret after laying the net, and the material electrostatic adsorption is not easy to separate, so that the bonding force of the nano melt-blown layer and the polyolefin skeleton can be guaranteed, avoiding the problem of separation, and also can improve the filtration efficiency of the filter material.
[0007] Preferably, the material of the nano meltblown layer includes polymer material and electret masterbatch; the mass ratio of the polymer material to the electret masterbatch is 95:5 to 97:3.
[0008] Preferably, the polymer material is selected from at least one of polypropylene, polyamide, polyester, polylactic acid and polyurethane.
[0009] Preferably, the polyolefin skeleton has a gram weight of 70 to 110 g / m 2 The weight of the nano meltblown layer is 5-20g / m2 The present invention adopts a low-weight nano melt-blown layer and a polyolefin skeleton to prepare a nano melt-blown composite filter material; this double-layer electret material increases the dust holding capacity of the composite filter material, enabling it to capture more tiny particles in the air, such as dust, bacteria, etc.
[0010] Preferably, the thickness of the polyolefin skeleton is 0.5-0.65 mm, and the thickness of the nano melt-blown composite filter material is 0.1-1 mm.
[0011] Preferably, the spinneret aperture used in step (1) meltblowing is 0.1-0.25 mm, the screw temperature is 200-280 ° C, the spinneret temperature is 220-300 ° C, the wind temperature is 250-310 ° C, the screen receiving distance is 150-250 mm, and the hot air flow rate is 600-1500 m 3 / h, air flow rate 15000~30000m 3 / h, meltblowing speed 5~20m / min.
[0012] Preferably, during the corona electret process in step (2), the vertical distance between the discharge end surface and the composite material is 3 to 20 cm.
[0013] Preferably, the voltage during corona electret in step (2) is 10 to 60 kV.
[0014] Preferably, in step (3), a cross-patterned roller or a small dot roller is used for ultrasonic compounding.
[0015] Preferably, the ultrasonic frequency during ultrasonic compounding in step (3) is 20 to 30 kHz.
[0016] Therefore, the present invention has the following beneficial effects: (1) A polyolefin skeleton with an electret but not electret is used as a laying layer, and a nano melt-blown layer is directly sprayed on the polyolefin skeleton. The skeleton and the nano melt-blown layer are simultaneously electreted, which can reduce the number of winding and unwinding of the nano melt-blown material, and the nano melt-blown material is not easy to stretch and deform, thereby improving the filtration efficiency of the filter material; (2) The present invention completes the electret of the skeleton and the electret of the meltblown material at one time, thereby avoiding damage and performance degradation during multiple processing processes; reducing the number of material processing times, improving production efficiency, and also reducing production costs; (3) A nano melt-blown composite filter material is prepared by using a low-weight nano melt-blown layer and a polyolefin skeleton; this double-layer electret material increases the dust holding capacity of the composite filter material, enabling it to capture more tiny particles in the air, such as dust, bacteria, etc.; (4) The polyolefin skeleton and the nano melt-blown layer are fixed by ultrasonic synchronous welding; this welding method improves the bonding strength and stability between the nano melt-blown layer and the substrate, avoids the influence of adhesives or hot pressing methods on the filtering performance of the nano melt-blown fiber and the problem of loose bonding that may result, and also avoids major damage to the substrate. DETAILED DESCRIPTION
[0017] The present invention is further described below in conjunction with specific implementation methods.
[0018] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.
[0019] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with specific implementation methods, but it should be understood that these descriptions are only to further illustrate the features and advantages of the present invention rather than to limit the claims of the present invention.
[0020] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0021] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0022] Overall embodiment: A method for preparing a nano melt-blown composite filter material comprises the following steps: (1) placing a polyolefin skeleton containing an electret but not electret on the surface of a melt-blown receiving mesh curtain, and melt-blowing a nano melt-blown layer on the polyolefin skeleton to obtain a composite material; (2) subjecting the composite material to corona electret charging; (3) Ultrasonic compounding is performed on the composite material after corona electret to obtain the nano melt-blown composite filter material.
[0023] As a specific implementation, the material of the nano meltblown layer includes a polymer material and an electret masterbatch; the mass ratio of the polymer material to the electret masterbatch is 95:5 to 97:3.
[0024] As a specific implementation, the polymer material is selected from at least one of polypropylene, polyamide, polyester, polylactic acid, and polyurethane.
[0025] As a specific embodiment, the polyolefin skeleton has a gram weight of 70 to 110 g / m 2 The weight of the nano meltblown layer is 5-20g / m 2 .
[0026] As a specific implementation, the thickness of the polyolefin skeleton is 0.5-0.65 mm, and the thickness of the nano melt-blown composite filter material is 0.1-1 mm; preferably, the thickness of the nano melt-blown composite filter material is 0.5-1 mm.
[0027] As a specific embodiment, the spinneret aperture used in step (1) meltblowing is 0.1-0.25 mm, the screw temperature is 200-280°C, the spinneret temperature is 220-300°C, the wind temperature is 250-310°C, the mesh curtain receiving distance is 150-250 mm, and the hot air flow rate is 600-1500 m 3 / h, air flow rate 15000~30000m 3 / h, meltblowing speed 5~20m / min.
[0028] As a specific implementation, during the corona electret in step (2), the vertical distance between the discharge end surface and the composite material is 3 to 20 cm.
[0029] As a specific implementation, the voltage during corona electret in step (2) is 10 to 60 kV.
[0030] As a specific implementation, in step (3), a cross-patterned roller or a small dot roller is used for ultrasonic compounding.
[0031] As a specific implementation, the ultrasonic frequency during ultrasonic compounding in step (3) is 20 to 30 kHz.
[0032] Embodiment 1: A method for preparing a nano melt-blown composite filter material comprises the following steps: (1) A polyolefin skeleton containing an electret but not an electret (purchased from Shanghai Jingfa PP / PE, 7256TS, weight 70 g / m 2, thickness 0.5mm) is placed on the surface of the melt-blown receiving mesh curtain, and the nano melt-blown layer is melt-blown on the polyolefin skeleton to obtain a composite material; the melt-blowing process is as follows: polypropylene (ExxonMobil, PP6936G2) with a mass ratio of 96:4 and an electret masterbatch (Jinhai Hi-Tech homemade masterbatch, ZJML013) are mixed and melt-extruded through a twin-screw extruder, and then the melt is passed through a melt-blown spinneret with an aperture of 0.15mm, the screw temperature is 230℃, the spinneret temperature is 250℃, the wind temperature is 265℃, the mesh curtain receiving distance is 200mm, and the hot air flow rate is 1000m 3 / h, air flow rate 20000m 3 / h, melt-blown speed 20m / min, nano melt-blown layer weight 5g / m 2 ; (2) subjecting the composite material to corona electret charging; during corona electret charging, the vertical distance between the discharge end surface and the composite material is 10 cm, and the voltage is 40 kV; (3) The composite material after corona electret bonding was ultrasonically compounded by a cross-patterned roller, and the ultrasonic frequency modulation power was 25 kHz (25,000 vibrations per minute), to obtain a nano melt-blown composite filter material with a thickness of 0.58 mm.
[0033] Embodiment 2: A method for preparing a nano melt-blown composite filter material comprises the following steps: (1) A polyolefin skeleton containing an electret but not an electret (purchased from Shanghai Jingfa PP / PE, 2143HF, weight 110 g / m 2 , thickness 0.65mm) is placed on the surface of the melt-blown receiving mesh curtain, and the nano melt-blown layer is melt-blown on the polyolefin skeleton to obtain a composite material; the melt-blowing process is as follows: polypropylene (ExxonMobil, PP6936G2) with a mass ratio of 96:4 and an electret masterbatch (Jinhai Hi-Tech homemade masterbatch, ZJML013) are mixed and melt-extruded through a twin-screw extruder, and then the melt is passed through a melt-blown spinneret with an aperture of 0.15mm, the screw temperature is 230℃, the spinneret temperature is 250℃, the wind temperature is 265℃, the mesh curtain receiving distance is 200mm, and the hot air flow rate is 1000m 3 / h, air flow rate 20000m 3 / h, melt-blown speed 20m / min, nano melt-blown layer weight 5g / m 2 ; (2) subjecting the composite material to corona electret charging; during corona electret charging, the vertical distance between the discharge end surface and the composite material is 10 cm, and the voltage is 40 kV; (3) The composite material after corona electret bonding was ultrasonically compounded by a cross-patterned roller, and the ultrasonic frequency modulation power was 25 kHz (25,000 vibrations per minute), to obtain a nano melt-blown composite filter material with a thickness of 0.71 mm.
[0034] Embodiment 3: A method for preparing a nano melt-blown composite filter material comprises the following steps: (1) A polyolefin skeleton containing an electret but not an electret (purchased from Shanghai Jingfa PP / PE, 7256TS, weight 70 g / m 2 , thickness 0.5mm) is placed on the surface of the melt-blown receiving mesh curtain, and the nano melt-blown layer is melt-blown on the polyolefin skeleton to obtain a composite material; the melt-blowing process is as follows: polypropylene (ExxonMobil, PP6936G2) with a mass ratio of 96:4 and an electret masterbatch (Jinhai Hi-Tech homemade masterbatch, ZJML013) are mixed and melt-extruded through a twin-screw extruder, and then the melt is passed through a melt-blown spinneret with an aperture of 0.15mm, the screw temperature is 230℃, the spinneret temperature is 250℃, the wind temperature is 265℃, the mesh curtain receiving distance is 200mm, and the hot air flow rate is 1000m 3 / h, air flow rate 20000m 3 / h, meltblown speed 10m / min, nano meltblown layer weight 10g / m 2 ; (2) subjecting the composite material to corona electret charging; during corona electret charging, the vertical distance between the discharge end surface and the composite material is 10 cm, and the voltage is 40 kV; (3) The composite material after corona electret bonding was ultrasonically compounded by a cross-patterned roller, and the ultrasonic frequency modulation power was 25 kHz (25,000 vibrations per minute), to obtain a nano melt-blown composite filter material with a thickness of 0.61 mm.
[0035] Embodiment 4: A method for preparing a nano melt-blown composite filter material comprises the following steps: (1) A polyolefin skeleton containing an electret but not an electret (purchased from Shanghai Jingfa PP / PE, 2143HF, weight 110 g / m 2 , thickness 0.65mm) is placed on the surface of the melt-blown receiving mesh curtain, and the nano melt-blown layer is melt-blown on the polyolefin skeleton to obtain a composite material; the melt-blowing process is as follows: polypropylene (ExxonMobil, PP6936G2) with a mass ratio of 96:4 and electret masterbatch (Jinhai Hi-Tech homemade masterbatch, ZJML013) are mixed and melt-extruded through a twin-screw extruder, and then the melt is passed through a melt-blown spinneret with an aperture of 0.15mm, the screw temperature is 230℃, the spinneret temperature is 250℃, the wind temperature is 265℃, the mesh curtain receiving distance is 200mm, and the hot air flow rate is 1000m 3 / h, air flow rate 20000m 3 / h, meltblown speed 10m / min, nano meltblown layer weight 10g / m 2 ; (2) subjecting the composite material to corona electret charging; during corona electret charging, the vertical distance between the discharge end surface and the composite material is 10 cm, and the voltage is 40 kV; (3) The composite material after corona electret charging is ultrasonically compounded by a cross-patterned roller, and the ultrasonic frequency modulation power is 25 kHz (25,000 vibrations per minute) to obtain a nano melt-blown composite filter material with a thickness of 0.75 mm.
[0036] Embodiment 5: A method for preparing a nano melt-blown composite filter material comprises the following steps: (1) A polyolefin skeleton containing an electret but not an electret (purchased from Shanghai Jingfa PP / PE, 7256TS, weight 70 g / m 2 , thickness 0.5mm) is placed on the surface of the melt-blown receiving mesh curtain, and the nano melt-blown layer is melt-blown on the polyolefin skeleton to obtain a composite material; the melt-blowing process is as follows: polypropylene (ExxonMobil, PP6936G2) with a mass ratio of 96:4 and an electret masterbatch (Jinhai Hi-Tech homemade masterbatch, ZJML013) are mixed and melt-extruded through a twin-screw extruder, and then the melt is passed through a melt-blown spinneret with an aperture of 0.15mm, the screw temperature is 230℃, the spinneret temperature is 250℃, the wind temperature is 265℃, the mesh curtain receiving distance is 200mm, and the hot air flow rate is 1000m 3 / h, air flow rate 20000m 3 / h, meltblown speed 5m / min, nano meltblown layer weight 20g / m 2 ; (2) subjecting the composite material to corona electret charging; during corona electret charging, the vertical distance between the discharge end surface and the composite material is 10 cm, and the voltage is 40 kV; (3) The composite material after corona electret bonding was ultrasonically compounded by a cross-patterned roller, and the ultrasonic frequency modulation power was 25 kHz (25,000 vibrations per minute), to obtain a nano melt-blown composite filter material with a thickness of 0.66 mm.
[0037] Comparative Example 1: The gram weight used in Example 1 is 70 g / m 2 The polyolefin skeleton is subjected to corona electret charging, with the vertical distance between the discharge end surface and the composite material being 10 cm and the voltage being 40 kV.
[0038] Comparative Example 2: The gram weight used in Example 2 is 110 g / m 2 The polyolefin skeleton is subjected to corona electret charging, with the vertical distance between the discharge end surface and the composite material being 10 cm and the voltage being 40 kV.
[0039] Comparative Example 3: A method for preparing a nano melt-blown filter material comprises the following steps: (1) Produced by meltblowing with a grammage of 5g / m 2The nano melt-blown material, the melt-blowing process is: the polypropylene (same as in Example 1) with a mass ratio of 96:4 and the electret masterbatch are mixed and melt-extruded through a twin-screw extruder, and then the melt is passed through a melt-blown spinneret with an aperture of 0.15 mm, the screw temperature is 230°C, the spinneret temperature is 250°C, the wind temperature is 265°C, the net curtain receiving distance is 200 mm, and the hot air flow rate is 1000 m 3 / h, air flow rate 20000m 3 / h, meltblowing speed 20m / min; (2) The nano melt-blown material is subjected to corona electret to obtain a nano melt-blown filter material with a thickness of 0.15 mm; during the corona electret, the vertical distance between the discharge end surface and the nano melt-blown material is 10 cm, and the voltage is 40 kV.
[0040] Comparative Example 4: A method for preparing a nano melt-blown filter material comprises the following steps: (1) Produced by meltblowing with a grammage of 10g / m 2 The nano melt-blown material, the melt-blowing process is: the polypropylene (same as in Example 1) with a mass ratio of 96:4 and the electret masterbatch are mixed and melt-extruded through a twin-screw extruder, and then the melt is passed through a melt-blown spinneret with an aperture of 0.15 mm, the screw temperature is 230°C, the spinneret temperature is 250°C, the wind temperature is 265°C, the net curtain receiving distance is 200 mm, and the hot air flow rate is 1000 m 3 / h, air flow rate 20000m 3 / h, meltblowing speed 10m / min; (2) The nano melt-blown material is subjected to corona electret to obtain a nano melt-blown filter material with a thickness of 0.2 mm; during the corona electret, the vertical distance between the discharge end surface and the nano melt-blown material is 10 cm, and the voltage is 40 kV.
[0041] Comparative Example 5: A method for preparing a nano melt-blown filter material comprises the following steps: (1) Produced by meltblowing with a grammage of 20g / m 2 The nano melt-blown material, the melt-blowing process is: the polypropylene (same as in Example 1) with a mass ratio of 96:4 and the electret masterbatch are mixed and melt-extruded through a twin-screw extruder, and then the melt is passed through a melt-blown spinneret with an aperture of 0.15 mm, the screw temperature is 230°C, the spinneret temperature is 250°C, the wind temperature is 265°C, the net curtain receiving distance is 200 mm, and the hot air flow rate is 1000 m 3 / h, air flow rate 20000m 3 / h, meltblowing speed 10m / min; (2) The nano melt-blown material is subjected to corona electret to obtain a nano melt-blown filter material with a thickness of 0.28 mm; during the corona electret, the vertical distance between the discharge end surface and the nano melt-blown material is 10 cm, and the voltage is 40 kV.
[0042] Comparative Example 6: A method for preparing a nano melt-blown composite filter material comprises the following steps: (1) Ordinary PET skeleton (purchased from Jinbaihe, KGT5070-2R, weight 70g / m 2 , thickness 0.45mm) is placed on the surface of the melt-blown receiving mesh curtain, and the nano melt-blown layer is melt-blown on the PET skeleton to obtain a composite material; the melt-blowing process is as follows: polypropylene (ExxonMobil, PP6936G2) with a mass ratio of 96:4 and the electret masterbatch are mixed and melt-extruded through a twin-screw extruder, and then the melt is passed through a melt-blown spinneret with an aperture of 0.15mm, the screw temperature is 230℃, the spinneret temperature is 250℃, the wind temperature is 265℃, the mesh curtain receiving distance is 200mm, and the hot air flow rate is 1000m 3 / h, air flow rate 20000m 3 / h, melt-blown speed 10m / min, nano melt-blown layer weight 5g / m 2 ; (2) subjecting the composite material to corona electret charging; during corona electret charging, the vertical distance between the discharge end surface and the composite material is 10 cm, and the voltage is 40 kV; (3) The composite material after corona electret bonding was ultrasonically compounded by a cross-patterned roller, and the ultrasonic frequency modulation power was 25 kHz (25,000 vibrations per minute), to obtain a nano melt-blown composite filter material with a thickness of 0.58 mm.
[0043] The experimental parameters in the above embodiments and comparative examples and the resistance and filtration efficiency of the prepared filter materials are shown in Table 1.
[0044] Table 1: Experimental parameters and filter material performance test results.
[0045] The filter materials in the above embodiments and comparative examples were used in filters, and the filtration performance of the filters was tested. The results are shown in Table 2 (Comparative Examples 3 to 5 only use nano melt-blown materials without support materials, and cannot be used as filters). Filter size: 250mm*210mm*45mm, conditions: fold height 43mm, fold number 44, filtration area 0.758m 2 ; Test conditions: Test air volume 380m 3 / h, test dust: A4 dust, final resistance 200Pa.
[0046] Table 2: Filter performance test results.
[0047] It can be seen from the test results in Table 1 and Table 2 that the composite filter material prepared by the method of the present invention in Examples 1 to 5 has high filtration efficiency, and when used in a filter, it has low filtration resistance, high filtration efficiency and dust holding capacity.
[0048] In Comparative Examples 1 and 2, only the polyolefin skeleton is used without being compounded with the nano melt-blown layer, and the filtration efficiency and dust holding capacity of the filter material are significantly reduced compared with those in the embodiment.
[0049] Only nano melt-blown materials are used in Comparative Examples 3 to 5. Although they can have a higher filtration efficiency, they have no supporting materials and cannot be used as filters.
[0050] In Comparative Example 6, a PET skeleton is used instead of the polyolefin skeleton in the present invention. Since the charging effect of the PET skeleton after electret charging is not as good as that of the polyolefin skeleton containing electret bodies, the skeleton is almost inefficient, resulting in a significant decrease in the filtration efficiency of the filter material compared with that in Example 1.
[0051] In each embodiment of the present invention, a polyolefin skeleton with an electret but not electret is used as a laying layer, a nano melt-blown layer is directly sprayed on the polyolefin skeleton, and the skeleton and the nano melt-blown layer are electret simultaneously, which can reduce the number of winding and unwinding of the nano melt-blown material, and the nano melt-blown material is not easy to stretch and deform, thereby improving the filtration efficiency of the filter material; at the same time, the present invention completes the electret of the skeleton and the electret of the melt-blown material at one time, avoiding damage and performance degradation during multiple processing processes; reducing the number of material processing times, improving production efficiency, and also reducing production costs; and the present invention uses a low-gram-weight nano melt-blown layer and a polyolefin skeleton to prepare a nano melt-blown composite filter material; this double-layer electret material increases the dust holding capacity of the composite filter material, so that it can capture more tiny particles in the air, such as dust, bacteria, etc. In each embodiment of the present invention, ultrasonic synchronous welding is used to fix the polyolefin skeleton and the nano melt-blown layer; this welding method improves the bonding strength and stability of the nano melt-blown layer and the substrate, avoids the influence of adhesives or hot pressing methods on the filtering performance of the nano melt-blown fiber and the problem of loose bonding that may be caused, and also avoids significant damage to the substrate.
[0052] The above content is a further detailed description of the technical solution of the present invention in combination with a specific preferred implementation method, and should not be understood as a limitation on the applicable scope of the present invention. For ordinary technicians in the field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the present invention, which should be deemed to fall within the scope of patent protection determined by the claims submitted for the present invention.
Claims
1. A method for preparing a nano melt-blown composite filter material, characterized in that: The steps include: (1) placing a polyolefin skeleton containing an electret but not electret on the surface of a melt-blown receiving mesh curtain, and melt-blowing a nano melt-blown layer on the polyolefin skeleton to obtain a composite material; (2) subjecting the composite material to corona electret charging; (3) Ultrasonic compounding is performed on the composite material after corona electret to obtain the nano melt-blown composite filter material.
2. The method for preparing the nano melt-blown composite filter material according to claim 1, characterized in that: The material of the nano meltblown layer includes a polymer material and an electret masterbatch; the mass ratio of the polymer material to the electret masterbatch is 95:5-97:
3.
3. The method for preparing the nano melt-blown composite filter material according to claim 2, characterized in that: The polymer material is selected from at least one of polypropylene, polyamide, polyester, polylactic acid and polyurethane.
4. The method for preparing the nano melt-blown composite filter material according to claim 1, characterized in that: The polyolefin skeleton has a gram weight of 70-110 g / m 2 The weight of the nano meltblown layer is 5~20g / m 2 .
5. The method for preparing the nano melt-blown composite filter material according to claim 1 or 4, characterized in that: The thickness of the polyolefin skeleton is 0.5-0.65 mm, and the thickness of the nano melt-blown composite filter material is 0.1-1 mm.
6. The method for preparing the nano melt-blown composite filter material according to claim 1, characterized in that: Step (1) The spinneret aperture used in meltblowing is 0.1~0.25mm, the screw temperature is 200~280℃, the spinneret temperature is 220~300℃, the air temperature is 250~310℃, the screen receiving distance is 150~250mm, and the hot air flow rate is 600~1500m 3 / h, air flow rate 15000~30000m 3 / h, meltblown speed 5~20m / min.
7. The method for preparing the nano melt-blown composite filter material according to claim 1, characterized in that: During the corona electret process in step (2), the vertical distance between the discharge end surface and the composite material is 3 to 20 cm.
8. The method for preparing the nano melt-blown composite filter material according to claim 1 or 7, characterized in that: The voltage during corona electret in step (2) is 10~60kV.
9. The method for preparing the nano melt-blown composite filter material according to claim 1, characterized in that: In step (3), a cross-patterned roller or a small dot roller is used for ultrasonic compounding.
10. The method for preparing the nano melt-blown composite filter material according to claim 1 or 9, characterized in that: The ultrasonic frequency during ultrasonic compounding in step (3) is 20-30 kHz.
Citation Information
Patent Citations
Highly charged, charge stable nanofiber web
CN101820968A
Energy increasing additive added multi-layer melt-blown composite filter material and preparation method thereof
CN106076000A
Nanofiltration filter element material as well as production process and application thereof
CN112807852A
Two-component composite electret fiber and preparation method and application thereof
CN115418744A
Efficient antibacterial multifunctional bi-component melt-blown filter material as well as preparation method and application thereof
CN116196698A